Patent plus: a blinded, randomised and extension study of riociguat plus sildenafil in pulmonary arterial hypertension - Galiè, Nazzareno; Grünig, Ekkehard (The European respiratory journal, 2015)
PATENT PLUS evaluated the safety and efficacy of riociguat in combination with sildenafil in pulmonary arterial hypertension patients. Patients receiving sildenafil (20 mg three times daily) were randomised to placebo or riociguat (up to 2.5 mg three times daily) for 12 weeks. The primary outcome was maximum change in supine systolic blood pressure (SBP) from baseline within 4 h of dosing. Secondary objectives comprised additional blood pressure, heart rate and exploratory efficacy variables, and safety. Patients could enter a long-term extension (LTE), where all patients received riociguat plus sildenafil. There was no difference in maximum change in supine SBP from baseline within 4 h between the riociguat (n=12) (mean±sd baseline: -20.2±15.3 mmHg; week 12: -20.7±18.0 mmHg) and placebo groups (n=6) (-7.6±3.9 and -20.2±12.9 mmHg, respectively). Changes in standing SBP and supine or standing diastolic blood pressure were also not different. Combination therapy showed no favourable effects on exploratory clinical parameters, including haemodynamics and exercise capacity. In the LTE, there were high rates of discontinuation due to hypotension and three (18%) deaths (not considered study drug-related by the investigator). There were potentially unfavourable safety signals with sildenafil plus riociguat and no evidence of a positive benefit/risk ratio. Concomitant use of riociguat with phosphodiesterase-5 inhibitors is therefore contraindicated. Sildenafil+riociguat in PAH: no evidence of a positive benefit/risk ratio and potentially unfavourable safety signals http://ow.ly/Hbmfh